ARTIFICIAL INTELLIGENCE IN SMART PHONES: A BOON or BANE - U, Pradeep Kumar; J, Kiran (International Journal of Psychosocial Rehabilitation, 2020)
The world today is depending upon the smart choices, smart perspectives, smart ideas and also looking forward to lead their lives smart using smart devices in the current scenario. With the help of AI we are driving our lives more in the easier form of the tasks we take up. Smart Phones are one among them which stimulates of human intelligence processes by machines, with the help of smart phones and the usage of the various AI Interfaces by various brands in the markets. The era of AI has begun in Education, Finance, Law, Manufacturing, Health care to provide better role in providing solutions to their queries.All these AI applications can be a BOON to the end users but at the same time can also be an BANE raising many Security and Ethical Concerns like abuse of AI tools, sophisticated machine learning tools, complications in the issues of security, Self Driven cars (Hackers) and Smartphones Usage and Applications. AI in smart phones can be as a medium of help to reduce the work/tasks but at the same time it can create lot of issues that could actually damage the Automation Systems due to many ethical concerns.